Optimizing Treatment Outcomes With Regorafenib: Personalized Dosing and Other Strategies to Support Patient Care. (12th May 2014) - Grothey, Axel; George, Suzanne; van Cutsem, Eric; Blay, Jean-Yves; Sobrero, Alberto; Demetri, George D.
Abstract: Regorafenib is an oral multikinase inhibitor that inhibits several kinases relevant to tumor biology in several cancers, including colorectal carcinoma (CRC) and gastrointestinal stromal tumor (GIST). In phase III trials, regorafenib significantly improved overall survival versus placebo in patients with metastatic CRC progressing after all available standard therapies, and significantly prolonged progression-free survival in patients with advanced GIST in whom at least imatinib and sunitinib had failed. Thus, this agent holds promise as a new standard of care for CRC and GIST patients after disease progression following all other approved therapies. The clinical trials reported to date show that this new treatment has a consistent adverse event profile that is quite different from that of traditional cytotoxic chemotherapies. The most common adverse events of regorafenib include dermatologic and mucosal toxicities (especially hand-foot skin reaction, rash, and oral mucositis), constitutional symptoms (e.g., fatigue, nausea, and weight loss), vascular effects (especially hypertension), and gastrointestinal symptoms (e.g., diarrhea). To help health care professionals anticipate and manage the adverse events associated with regorafenib, we describe our experiences in clinical trials and show that such toxicities can be effectively managed with close observation of patients from initiation of dosing, along with prompt appropriate interventions, including dose modifications, if necessary. Abstract : Regorafenib is a novel oral agent with documented efficacy in advanced colorectal cancer. It has a characteristic adverse event profile that consists of hand-foot skin reaction, fatigue, diarrhea, hypertension, and other less common events. The authors detail practical management strategies of these adverse events to optimize patient care and maximize the clinical benefit patients can derive from regorafenib.